2016
DOI: 10.1007/s11032-016-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput single nucleotide polymorphism (SNP) identification and mapping in the sesame (Sesamum indicum L.) genome with genotyping by sequencing (GBS) analysis

Abstract: Sesame (Sesamum indicum L. syn. Sesamum orientale L.) is considered to be the first oil seed crop known to man. Despite its versatile use as an oil seed and a leafy vegetable, sesame is a neglected crop and has not been a subject of molecular genetic research until the last decade. There is thus limited knowledge regarding genome-specific molecular markers that are indispensible for germplasm enhancement, gene identification, and marker-assisted breeding in sesame. In this study, we employed a genotyping by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Zhang et al [ 49 ] reported a SNP map comprised of 3041 bins including 30,193 SNPs in 13 LGs. Uncu et al [ 50 ] published an improved map of 13 LGs encompassed 432 markers (420 SNPs, 12 SSRs). In the present study, a genotyping by sequencing (GBS) approach was employed for high-throughput SNP identification and genotyping, then a high density bin map was constructed, which consisted of 1184 bins (13,679 SNPs), with an average of 0.918 cM between adjacent bins, while the bin marker density was similar to the map density of one bin per 0.98 cM described by Zhang et al [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 49 ] reported a SNP map comprised of 3041 bins including 30,193 SNPs in 13 LGs. Uncu et al [ 50 ] published an improved map of 13 LGs encompassed 432 markers (420 SNPs, 12 SSRs). In the present study, a genotyping by sequencing (GBS) approach was employed for high-throughput SNP identification and genotyping, then a high density bin map was constructed, which consisted of 1184 bins (13,679 SNPs), with an average of 0.918 cM between adjacent bins, while the bin marker density was similar to the map density of one bin per 0.98 cM described by Zhang et al [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping By Sequencing (GBS) has allowed high-throughput identification of molecular markers in the rose (Heo et al, 2017 ), apple (Norelli et al, 2017 ), pepper (Taranto et al, 2016 ), and pigeonpea (Saxena et al, 2017 ) at low costs (Voss-fels and Snowdon, 2016 ). The success of GBS in maize (Elshire et al, 2011 ), potato (Uitdewilligen et al, 2013 ), sesame (Uncu et al, 2016 ), and wheat (Poland et al, 2012 ; Kobayashi et al, 2016 ) suggest a role for the technique in non-model specialty crops. This technique is based on the reduction of genome complexity through methylation-sensitive restriction enzymes (Elshire et al, 2011 ), making it possible to search for polymorphisms in species with large genomes, high diversity, or without a reference genome (Poland and Rife, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an orphan or neglected crop, a high-density genetic map in sesame is still limited. Six dense SNP genetic maps have been so far constructed for sesame (Mei et al, 2017; Uncu et al, 2016; Wu et al, 2014; Wang et al, 2016; Zhang et al, 2013a; 2016). Most of these six genetic maps have been applied for QTL mapping using reduced representation genome sequencing (RRGS), while only the genotyping-by-sequencing (GBS) generated 770 SNPs and 50 SSRs were used to construct the first sesame linkage map (Uncu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Six dense SNP genetic maps have been so far constructed for sesame (Mei et al, 2017; Uncu et al, 2016; Wu et al, 2014; Wang et al, 2016; Zhang et al, 2013a; 2016). Most of these six genetic maps have been applied for QTL mapping using reduced representation genome sequencing (RRGS), while only the genotyping-by-sequencing (GBS) generated 770 SNPs and 50 SSRs were used to construct the first sesame linkage map (Uncu et al, 2016). Moreover, SSR markers widely used for genetic diversity and association mapping of germplasm lines to analyze quantitative traits or tagging to the various disease-related genes (Li et al, 2014; Liu et al, 2015; Wu et al, 2014; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%